Does Servant Leadership Behavior Induce Positive Behaviors? A Conceptual Study of Servant Leadership, Psychological Safety and Turnover Intention - Ahmed Brohi, Noor; Hamzah Jantan, Amer; Adal Mehmood, Sultan; Ahmed Khuhro, Mansoor; Saood Aktar, Muhammad; ., . (International Journal of Engineering and Technology, 2018)
In this paper, we examine how servant leadership and psychological safety may enlighten our understanding of human mechanisms that affect follower outcomes. Servant leadership style as penned by Robert Greenleaf that servant leaders guide followers to adopt the behavior of their leaders by putting others needs above their own. From emerging research on servant leadership, we proposed a model contending that servant leaders increase employeesâ€™ psychological safety that organization is a safe place to speak up ideas, opinions and take decisions, which directly influences Employeesâ€™ turnover intention. As proposed, servant leadership will be negatively related to Employeesâ€™ turnover intention and positively related to psychological safety. Psychological safety will mediate the relationship between servant leadership and turnover intention.Â